PENGATURAN INDUSTRI PERTAHANAN TERKAIT INVESTASI ASING (REGULATION ON DEFENSE INDUSTRY RELATED TO FOREIGN INVESTMENT) - Adi Haryono (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2017)
Diverse foreign investment schemes on defense industry in various countries are undergoing reform stage in order to recover domestic industry as well as to create sustainable industries. The transformation evolves in investment regulations and industry governance. This research use a normative juridical approach on the open and closed defense industry related to foreign investment, and on government role to create sustainable Joint Venture (JV). The Government has regulate level of participation of foreign investor on defense industries, based on strategic value level of defense industry’s cluster, thru level of control toward foreign investor in defense industry, starting from 0 percent to maximum 49 percent for closed sector under JV with State Owned Enterprise (SOE) for conditional open sector, and to maximum of 100 percent for open sector. Law No. 16 of 2012 on Defense Industry stipulates that the Industry of Key Equipment is non-accessible for foreign participation, while Law No. 25 of 2007 on Direct Investment, stipulates that the industry of weaponry, explosive device, gunpowder, and combat equipment, are non-accessible for foreign participation, and as a consequence harmonization of the two Laws is of necessity. To create sustainable JV, planning and control over JV by the government is crucial. Government thru Defense Industry Policy Committee (KKIP), determines on which industrial sector is economical and has competitive edge to defense industry and also determines which SOE and foreign partner will run the organization of JV. Control over JV with 51% of shares owned by SOE will be conducted according to Law No. 40 of 2007 on Limited Liability Company. AbstrakBerbagai skema PMA industri pertahanan di berbagai negara mengalami tahapan reformasi demi tercapainya revitalisasi industri dalam negeri maupun terciptanya industri yang berkesinambungan. Reformasi yang dilakukan meliputi peraturan penanaman modal dan tata kelola industri. Penelitian ini merupakan penelitian yuridis normatif tentang bidang usaha yang terbuka dan tertutup bagi PMA di industri pertahanan, dan bagaimana pemerintah membentuk Joint Venture(JV) yang berkesinambungan. Pemerintah telah mengatur tingkat partisipasi PMA di industri pertahanan berdasarkan tingkat nilai strategis suatu klaster industri pertahanan, melalui derajat pengendalian pihak asing di suatu perseroan pertahanan, dari sektor tertutup atau 0%, bersyarat di bawah BUMN hingga 49%, dan sektor terbuka hingga 100%. UU No. 16 Tahun 2012 tentang Industri Pertahanan mengatur bahwa Industri Alat Utama merupakan Industri yang tertutup bagi partisipasi asing, sementara UU No. 25 Tahun 2007 tentang Penanaman Modal mengatur bahwa industri senjata, mesiu, alat peledak, dan peralatan perang tertutup bagi asing, sehingga harmonisasi peraturan diperlukan. Untuk membentuk JV yang berkesinambungan, perencanaan Pemerintah dan pengendalian JV memegang peranan penting. Penentuan sektor industri pertahanan yang berdaya saing dan ekonomis dilakukan oleh Komite Kebijakan Industri Pertahanan (KKIP), termasuk penentuan BUMN dan Mitra PMA yang akan menjalankan organ perseroan JV. Pengendalian JV yang 51% sahamnya dimiliki oleh BUMN, akan dilakukan sesuai UU No. 40 Tahun 2007 tentang Perseroan Terbatas.